Absence of evidence is not evidence of absence: Nanopore sequencing and complete assembly of the European lobster (Homarus gammarus) mitogenome uncovers the missing nad2 and a new major gene cluster duplication - Gan, Han; Grandjean, Frederic; Jenkins, Tom; Austin, Christopher (Figshare, 2019)
Abstract Background The recently published complete mitogenome of the European lobster (Homarus gammarus) that was generated using long-range PCR exhibits unusual gene composition (missing nad2) and gene rearrangements among decapod crustaceans with strong implications in crustacean phylogenetics. Such atypical mitochondrial features will benefit greatly from validation with emerging long read sequencing technologies such as Oxford Nanopore that can more accurately identify structural variation. Results We re-sequenced the H. gammarus mitogenomeÂ on an Oxford Nanopore Minion flowcell and performed a long-read only assembly, generating a complete mitogenome assembly for H. gammarus. In contrast to previous reporting, we found an intact mitochondrial nad2 gene in the H. gammarus mitogenome and showed that its gene organization is broadly similar to that of the American lobster (H. americanus) except for the presence of a large tandemly duplicated region with evidence of pseudogenization in one of each duplicated protein-coding genes. Conclusions Using the European lobster as an example, we demonstrate the value of Oxford Nanopore long read technology in resolving problematic mitogenome assemblies. The increasing accessibility of Oxford Nanopore technology will make it an attractive and useful tool for evolutionary biologists to verify new and existing unusual mitochondrial gene rearrangements recovered using first and second generation sequencing technologies, particularly those used to make phylogenetic inferences of evolutionary scenarios.